ANALISIS HUBUNGAN INTEGRASI PASAR MODAL KAWASAN ASEAN-5 - Suryandani, Wulan (BBM (Buletin Bisnis & Manajemen), 2018)
ASEAN is an intergovernmental organization in Shouteast Asia, working together on economic and political issues. With the establishment of economic relations, one of them in the field of capital market will give effect to the movement of capital market indices in each country in the ASEAN region. Knowing the integration of capital market in ASEAN region can help investors in determining which capital markets will be used to form international diversification so that it can give potential benefits. In this study analyzed the level of capital market integration between ASEAN-5 capital markets from 2006 to 2017 years. The method of analysis used in this study is the Augmented Dickey Fuller (ADF), Johansen Cointegration, VAR estimation (Vector Auto Regression), and Granger Causality Test. By using this method of analysis it is concluded that there is a long term relationship between capital market integration in ASEAN-5. And in this study we found that there is a causal relationship between capital market in ASEAN-5, although not entirely. Keywords : Capital Market Integration, Augmented Dickey Fuller, VAR Estimate, Granger Causality, Johansen Cointegration, International Diversification, ASEAN